Zakat and poverty alleviation: Al-Hayat Relief Foundation contributions in Ogun State, Nigeria: an overview - Ololade, Ahmed Bilqis; Johari, Fuadah; Abd Wahab, Kalsom Bintu (Universiti Sains Islam Malaysia, 2024)
Islam being a universal religion meant for the entire humanity, its agenda regarding poverty is not limited to Muslims, but covers the entire populace of the world. Indeed, evaluating the potential of Islamic economic tool (zakat) to alleviating the challenges of poverty is a global alternative directive. This paper intends to highlight the roles of zakat towards alleviating poverty through the roles of the Institution of al-Hayat Foundation and past literatures to analyze its contributions. Using al-hayat unpublished report of zakat collected and distributed to the various recipients from year 2005-2012, it shows that the more the zakat collected, the more the zakat distributed to the recipients with the poor and the needy taken the better part. Although, wealthy individuals must be orientated and encouraged to pay their zakat in order to enhance sustaining the foundation. Productive recipients must also be encouraged to become skillful entrepreneur and independent.